Encouraging participation in public discourse through online writing in ESL instruction - Chan, Mei Yuit; Yap, Ngee Thai (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2010)
In recent years, writing instructors have started to adopt pedagogies that integrate classroom writing with happenings outside the classroom (see Weisser, 2001; Flower, 2008; Mathieu, 2005). The goal of writing instruction is no longer limited to competence in terms of language, style and techniques, but is expanded to encompass civic literacy. This orientation of writing especially at university level intertwines with the aim of higher education to produce individuals who are empowered to contribute towards a better world through participation in public discourse. In a study conducted at Universiti Putra Malaysia, 1,400 students were required to write publicly in an online forum on issues that affect the lives of the students and the community in which they belong. At the end of the course, the students completed a survey aimed at identifying the extent to which the writing course that adopted a public orientation was effective in socialising students towards becoming independent participants of online discussion. Specifically, the study sought to uncover the students‘ perceptions on whether they had improved in their writing skills, their confidence to write in English in the public sphere, the effect of audience on their writing, the value of participation in online public discussions, their intention to participate in the future, and the reasons for future participation or non-participation. This paper presents the results of the study and discusses the contribution of a public orientation in ESL writing instruction in fostering ability and motivation to participate in public discourse among university students.